2019
DOI: 10.1186/s12887-019-1683-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NIV-NAVA and NCPAP in facilitating extubation for very preterm infants

Abstract: Background Various types of noninvasive respiratory modalities that lead to successful extubation in preterm infants have been explored. We aimed to compare noninvasive neurally adjusted ventilatory assist (NIV-NAVA) and nasal continuous positive airway pressure (NCPAP) for the postextubation stabilization of preterm infants. Methods This retrospective study was divided into two distinct periods, between July 2012 and June 2013 and between July 2013 and June 2014, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 40 publications
(42 reference statements)
1
24
0
1
Order By: Relevance
“…These authors found that the re-intubation rate was significantly lower in the NIV-NAVA group (12% vs 50%, P ¼ .02) despite a significantly longer duration of invasive ventilation (5.5 vs 12.4 d, P ¼ .04). Consistent with these findings, Lee and colleagues 51 reported a reduction in extubation failure for infants < 30 weeks gestational age who received NIV compared with CPAP (6% vs 38%, P ¼ .041). Although these results are encouraging, both studies were retrospective by design and had a limited sample size.…”
Section: Noninvasive Ventilationmentioning
confidence: 58%
“…These authors found that the re-intubation rate was significantly lower in the NIV-NAVA group (12% vs 50%, P ¼ .02) despite a significantly longer duration of invasive ventilation (5.5 vs 12.4 d, P ¼ .04). Consistent with these findings, Lee and colleagues 51 reported a reduction in extubation failure for infants < 30 weeks gestational age who received NIV compared with CPAP (6% vs 38%, P ¼ .041). Although these results are encouraging, both studies were retrospective by design and had a limited sample size.…”
Section: Noninvasive Ventilationmentioning
confidence: 58%
“…Yagui et al conducted a RCT ( n = 123) comparing NIV-NAVA vs. NCPAP as the primary support in infants with BW <1500 g. There was no difference noted in the primary outcome of need for intubation prior to 72 hours of life, or for the secondary outcome of BPD, between the two groups [ 82 ]. Other small RCTs have shown that NIV-NAVA is as effective as NCPAP in preventing extubation failure, but large RCTs studying the outcome of BPD in extremely preterm infants are needed before NIV-NAVA can be routinely recommended [ 83 , 84 , 85 , 86 , 87 ].…”
Section: Non-invasive Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…NAVA improves synchrony in patients with respiratory support by detecting the electrical activity of the diaphragm and may offer potential benefits in neonatal ventilation. Again, it has been shown to be superior to CPAP in facilitating extubation in preterm infants in small studies [5]. So, it seems that a synchronised modality of consistent pressure delivery might be superior to conventional modalities of NIV, but their use across neonatal units is still limited.…”
Section: Respiratory Support For the Preterm Infant-changing Paradigmmentioning
confidence: 99%